2017
DOI: 10.1021/acs.biochem.7b00504
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Stability of the Histone H2A–H2B Dimer by H2A Tyr57 Phosphorylation

Abstract: Histone H2A and H2B form a H2A-H2B heterodimer, which is a fundamental unit of nucleosome assembly and disassembly. Several posttranslational modifications change the interface between the H2A-H2B dimer and the H3-H4 tetramer and regulate nucleosome stability. However, posttranslational modifications associated with the interface between H2A and H2B have not been discussed. In this paper, it is shown that Tyr57 phosphorylation in H2A strongly influences H2A-H2B dimerization. Tyr57-phosphorylated H2A was chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The phosphorylation of H2A by the CK2 kinase at tyrosine 57 is required for the regulation of transcription elongation 41 and additionally affects H2B monoubiquitination and trimethylation of lysine in H3 41,42 . Phosphorylation of H2A by CK2 on this helix results in a loss of binding affinity between H2A and H2B due to steric hindrance by the phosphorylation site 43 . To confirm whether COMMD4 bound only to H2B or to both H2A and H2B, we performed an in vitro binding assay between COMMD4 and H2A or H2B, which demonstrated that COMMD4 bound to both H2A and H2B, but preferentially bound to H2B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of H2A by the CK2 kinase at tyrosine 57 is required for the regulation of transcription elongation 41 and additionally affects H2B monoubiquitination and trimethylation of lysine in H3 41,42 . Phosphorylation of H2A by CK2 on this helix results in a loss of binding affinity between H2A and H2B due to steric hindrance by the phosphorylation site 43 . To confirm whether COMMD4 bound only to H2B or to both H2A and H2B, we performed an in vitro binding assay between COMMD4 and H2A or H2B, which demonstrated that COMMD4 bound to both H2A and H2B, but preferentially bound to H2B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We calibrated the simulation temperature firstly by performing the REMD simulations on H2A‐H2B with 28 replicas ranging from 151.5 to 226.1 K to determine the folding temperature T f . The T f of H2A‐H2B is about 1.62 (194.84 K) in our model, which corresponds to the melting temperature (about 60°C) of H2A‐H2B in the experiment 28 . Therefore, the simulation temperature 1.40 (168.39 K in our model) will be comparable to the room temperature (298 K in experiment).…”
Section: Methodsmentioning
confidence: 53%
“…This work showed that the Y57ph PTM destabilizes the H2AÀ H2B dimer, and thus, the entire nucleosome. [374] In another interesting study, the role of a recently discovered glutamine methylation [375] (Qme) at site 104 of H2A was examined by NCL synthesis, finding that the mark was destabilizing to the nucleosome. [376] Histone H3 also exhibits a variety of interesting PTMs, which have been studied by chemical synthesis.…”
Section: Chemically Synthesized Histonesmentioning
confidence: 99%